Structure and electrochemical studies on the complexation of hexacyclohexanocucurbit[6]uril with lead ion. (1st March 2018) - Yang, Liguo; Wang, Xin; Zhang, Yonghui; Li, Zaoming; Song, Haixiang; Niu, Yongsheng; Tao, Zhu; Liu, Qingyun; Xiao, Xin
Graphical abstract: A novel supramolecular complex was synthesized and characterized by X-ray diffusion. The interaction between Cy6 Q[6] and Pb 2+ cation was studied through the crystal structure in the solid state and electronic chemistry analysis in aqueous solution. Abstract: A new supramolecular complex [Pb2 (C60 H72 N24 O12 )Cl(NO3 )3 (H2 O)3 ]2 (1 ) has been synthesized through slow evaporation of the volatiles in air at room temperature from a mixed solution of Cy6 Q[6] and Pb(NO3 )2 . The interaction between Cy6 Q[6] and Pb 2+ cation has been studied by single crystal X-ray diffraction studies in the solid state and by electrochemical analysis in aqueous solution. Experimental results showed the ratio of Cy6 Q[6] and Pb 2+ in complex1 to be 1:2.